2016
DOI: 10.1016/j.appdev.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of technology and technology-focused parenting: Associations with youth screen time

Abstract: In the present study we propose a model linking parental perceptions of technology to technology-related parenting strategies to youth screen time, and, finally, to internalizing and externalizing problem behaviors. Participants were 615 parents drawn from three community samples of families with children across three developmental stages: young childhood, middle childhood, and adolescence. The model was tested at each stage with the strongest support emerging in the young childhood sample. One component of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 56 publications
3
63
0
5
Order By: Relevance
“…Parents believed that screen time taught children to disrespect parental authority and encouraged disobedience. This dissonance that parents experience is not addressed by current screen time interventions (Sanders, Parent, Forehand, Sullivan, & Jones, 2016). Parents knew that a healthy balance of media use is important, but broader social contexts (marital discord and economics) challenged the enforcement of familial screen time rules and rules were often permissive.…”
Section: Discussionmentioning
confidence: 99%
“…Parents believed that screen time taught children to disrespect parental authority and encouraged disobedience. This dissonance that parents experience is not addressed by current screen time interventions (Sanders, Parent, Forehand, Sullivan, & Jones, 2016). Parents knew that a healthy balance of media use is important, but broader social contexts (marital discord and economics) challenged the enforcement of familial screen time rules and rules were often permissive.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher sets out different ways in which the screen time or time to watch the gadget must be carefully arranged (Muhamad Syazali, 2015). Because of several studies (Hale & Guan, 2015;Hewitt et al, 2018;Hinkley, Carson, Kalomakaefu, & Brown, 2017;Lauricella, Wartella, & Rideout, 2015;Sanders, Parent, Forehand, Sullivan, & Jones, 2016) suggesting the use of ICT should be considered because it interferes with sleep and concentration in carrying out daily routines. Limiting screen time will have a good effect on student performance (Salomon & Ben-David Kolikant, 2016).…”
Section: Calculation Of Chart Questionnaire Use Of "Ict Child Friendlmentioning
confidence: 99%
“…Since parents ultimately are their children's gatekeepers when it comes to accessing and using technology (Hamilton et al 2016), exploring parental attitudes is an important aspect of this study, especially since culturally differentiated views on technology use remain under-explored (Atkin et al 2014) Studies of screen time reported an increase in obesity among young children (see e.g. Hamilton et al 2016;Sanders et al 2016). The ability of parents to control screen time decreases with age, making the exploration of parental attitudes a matter of particular importance when it comes to families with young children (Hamilton et al 2016).…”
Section: Parental Attitudes To Technologymentioning
confidence: 99%